Challenging the traditional axioms : translation into a non-mother tongue - Pokorn, Nike K. (Nike Kocijančič) (Benjamins translation library, 2005)
Translation into a non-mother tongue or inverse translation, especially of literary texts, has always been frowned upon within Translation Studies in Western cultures and regarded by literary scholars and linguists as an activity of dubious worth, doomed to fail. The study, which received an award from EST in 2001, sets out to challenge the established view and to critically question some of the axiomatic assumptions of Western theorists. Its challenge is supported by extensive empirical research involving reader response to translations of specific literary texts. The conclusion reached is th.